2017
DOI: 10.1080/13561820.2016.1250726
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional education in a student-led emergency department: A realist evaluation

Abstract: This paper reports a realist evaluation undertaken to identify factors that facilitated or hindered the successful implementation of interprofessional clinical training for undergraduate students in an emergency department. A realist evaluation provides a framework for understanding how the context and underlying mechanisms affect the outcome patterns of an intervention. The researchers gathered both qualitative and quantitative data from internal documents, semi-structured interviews, observations and questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 22 publications
1
22
0
5
Order By: Relevance
“…In 1998 the concept of interprofessional education (IPE) was introduced at the institution and as a result, three clinical education wards were established at three different teaching hospitals. A few years later a clinical education emergency department was also established (Ericson et al, 2017;Ponzer et al, 2004). These IPE learning environments for students from both the undergraduate medical programme and the nursing programme were well established and integrated within the organisation at the time of the study.…”
Section: Study Settingmentioning
confidence: 99%
“…In 1998 the concept of interprofessional education (IPE) was introduced at the institution and as a result, three clinical education wards were established at three different teaching hospitals. A few years later a clinical education emergency department was also established (Ericson et al, 2017;Ponzer et al, 2004). These IPE learning environments for students from both the undergraduate medical programme and the nursing programme were well established and integrated within the organisation at the time of the study.…”
Section: Study Settingmentioning
confidence: 99%
“…Clinical teaching is provided in the designated part of the hospital's ED for teams involving medical, nursing, and paramedical learners. The Ericson (2017) study showed that the emergency ward provided an excellent environment for IPE (14).…”
Section: Interprofessional Education (Ipe)mentioning
confidence: 99%
“…Twenty studies used a combination of quantitative data (questionnaires with Likert scale) and qualitative data (semi-structured interviews, observations, and critical incident method) to study their research questions (Freeth et al 2001;Hylin et al 2007;Mackenzie et al 2007;Morison and Jenkins 2007;Hallin et al 2009;Jakobsen et al 2010;Hylin et al 2011;Jakobsen et al 2011;Dando et al 2012;Ericson et al 2012;Lachmann et al 2012;Brewer and Stewart-Wynne 2013;Lachmann et al 2013;Hood et al 2014;Lachmann et al 2014;Morphet et al 2014;McGettigan and McKendree 2015;Ericson et al 2017). Seven studies used solely qualitative methods (Freeth and Nicol 1998;Fallsberg and Hammar 2000;Jacobsen et al 2009;Carlson et al 2011;Sommerfeldt et al 2011;Falk et al 2013;Hallin and Kiessling 2016).…”
Section: Design and Quality Of The Studiesmentioning
confidence: 99%